PENGEMBANGAN MEDIA PLEACE O’CLOCK PADA POKOK BAHASAN PECAHAN UNTUK SISWA SDN 4 JENGGIK - Ahmad Yasar Ramdan; Atiaturrahmaniah Atiaturrahmaniah (Universitas Muhammadiyah Surakarta, 2019)
This research aimed to find out the validity and effectiveness of pleace o’clock media as the developed products and to find out students’ achievement test. The development procedures used Borg and Gall model which had been modified into 8 stages. The subjects of this study were 23 of fifth grade (V) students of SDN 4 Jenggik. Data collection techniques used in this study were validation sheets, achievement test, and students’ response questionnaire. The results from expert validators, or from media experts obtained 55 scores, then the average scores were 4.23 which were indicated as